Design and development of ladder new mechanism - Suparman, Samsuddin (2007)
Nowadays, people do not realize that current mechanism of ladder is unsafe and unstable. The statistics show that numerous number of ladder accident happen every year. This research is about to design and develop a new safer and stable mechanism of ladder in order to change the dangerous mechanism of current ladder. The project starts with reviewing the potential mechanism that can be applied and the most simple and effective mechanism will be selected. After finalized the best design among alternatives design, fabrication processes then followed. The structure was analyzed by using software in order to satisfy the strength of the design structure. The processes involved in this project are cutting process, drilling process, sheet metal process, joining process and surface finish process. After the product was fabricated, test run is applied in order to know the capability and ability. From the test .run analysis, the new mechanism of ladder can successfully reach 2 meters height in stable condition. It also can withstand the applied maximum load. So, the objectives of the project have been successfully achieved. Thus, this project has provided a new mechanism of ladder that is more safe and stable during the application. Otherwise, there are some recommendations that can be applied to the new mechanism of ladder to improve the capability. The amplification system should be added to the mechanism in order to minimize the force consumption and optimize the reaction of the new ladder mechanism. Other than that, this type of mechanism can be applied for others system such as jack mechanism, cranes and trolley.